ESTIMATE THE EFFICIENCY OF TWO TECHNICS OF THE OPERATIONS WITH POLYPROPYLENE IMPLANTS FOR ANTERIOR PELVIC ORGANS PROLAPSE BY WOMEN - Игорь Александрович Эйзенах; Александра Константиновна Пичигина; Галина Анатольевна Лапий; Вадим Гельевич Мозес; Вероника Валерьевна Власова; Кира Борисовна Мозес; Михаил Юрьевич Солуянов; Федор Андреевич Ракитин (Medicina v Kuzbasse, 2021)
Аim of research – to estimate the efficiency of two technics of the operations with polypropylene implants for anterior pelvic organs prolapse by women with classification POP-Q and ultrasonic method.